Community policing and proximity public security: An analysis of the effectiveness of the Ronda no Bairro Program in the municipality of Maceió, Alagoas, Brazil (Research, Society and Development, 2026)
The Programa Ronda no Bairro (PRB) is a public policy of proximity-based security in the State of Alagoas, aimed at violence prevention, the approximation between security forces and the community, social assistance, and the requalification of urban spaces. In Maceió, the program operates in strategic areas, such as Orla, Centro, Benedito Bentes, and Jacintinho, through integrated actions involving security agents, social teams, and public institutions. The general objective of this study was to propose a practical and scientifically grounded analysis of the feasibility and potential effects of implementing the Programa Ronda no Bairro in the Feirinha do Tabuleiro region, in Maceió. The methodological design adopted a qualitative approach, with exploratory and descriptive purposes, using bibliographic research, documentary research, statistical data collection, and an operational and financial feasibility study. The study analyzed aspects related to local criminality, the required operational structure, patrol modalities, estimated costs, and the integration between the PRB and the Military Police of the State of Alagoas (PMAL). The results indicate that implementing the PRB in Feirinha do Tabuleiro is operationally and financially feasible, with potential to reduce crime, increase the perception of security, requalify urban space, and strengthen the relationship between the police and the community. It is concluded that expanding the program to this locality represents a strategic alternative for improving proximity-based public security in Maceió.